Effect of Vitamin D Supplementation on Serum Lipid Profiles in Children and Adolescence: A Meta-analysis - Bita Amiri; Kokab Namakin; Maryam Soltani; Sameep Shetty; Seyed Mohammad Riahi (Mazandaran University of Medical Sciences, 2022)
Background: Vitamin D deficiency is an important risk factor for some chronic diseases. Some reports suggested that there is an interrelationship between lipids and cholecalciferol. Objectives: This meta-analysis was conducted to summarize the existing evidence of randomized controlled trials (RCTs) to evaluate the effect of vitamin D supplementation on lipid profiles in children and adolescents. Methods: In this systematic review and meta-analysis, databases, such as Web of Science, PubMed, Scopus, Google Scholar, EMBASE, ScienceDirect, Magiran, and SID were searched for studies up to December 21, 2019. This study was conducted according to PRISMA guidelines. I-square was used to measure the existing heterogeneity through included articles. Considering heterogeneity among articles, random-effect models were applied to pool Standardized Mean Differences (SMD) as overall effect size. Study eligibility criteria included children and adolescents (<18 years) and evaluation of the association between vitamin D and lipid profile. A P<0.05 was considered statistically significant and the analyses were conducted by STATA 14.0. Results: A total of 13 trials (number of participant=173) were included in the current meta-analysis. The SMD was 0.23, the vitamin D supplementation was associated with a significant slight increase in high-density lipoproteins (HDL) levels in children and adolescents (SMD 0.23; 95% CI, 0.02, 0.45, P=0.036; I2=57.7%, Egger's P=0.554). We found no significant association between vitamin D supplementation and LDL-cholesterol (SMD -0.10; 95% CI, −0.29, 0.09, P=0.310; I2=0.0%, Egger's P=0.689), total cholesterol (SMD -0.01; 95% CI, −0.20, 0.18, P=0.926; I2=0.0%, Egger's P=0.005), and triglycerides (SMD -0.10; 95% CI, − 0.22, 0.02, P=0.093; I2=0.0%, Egger's P=0.160) levels. Conclusions: Vitamin D can marginally increase HDL levels, without any significant effect on LDL-C, TG, and TC levels.